I) \( 27 \div 3+[66 \div 6-(28 \div 14 \times 2)+30 \div 6]-10= \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
First, let's break down the expression step by step. 1. Start with the operations inside the brackets: - \( 66 \div 6 = 11 \) - \( 28 \div 14 = 2 \), then \( 2 \times 2 = 4 \) - \( 30 \div 6 = 5 \) Now substitute these results back into the expression: \[ 27 \div 3 + [11 - 4 + 5] - 10 \] 2. Calculate \( 27 \div 3 = 9 \). 3. Now solve inside the brackets: - \( 11 - 4 + 5 = 11 - 4 = 7 \) - Then \( 7 + 5 = 12 \) 4. Now plug this back into the expression: \[ 9 + 12 - 10 \] 5. Finally, calculate: - \( 9 + 12 = 21 \) - Then \( 21 - 10 = 11 \) Thus, the final result is \( \boxed{11} \).